Enhancing wear resistance of inconel 601 through pack alumunizing coating and advanced lubrication environments - Mehmet Tayyip Özdemir; Recep Demirsöz; Refik Polat (Discover Materials)
Abstract Inconel 601 alloy is a material widely used at high temperatures. One of the most important mechanical properties to consider for some of the materials used in these areas is wear. Wear that occurs at the contact points between parts both causes material loss and reduces material performance. For this reason, coatings and new lubricants are used on material surfaces to reduce wear. In this study, nanoparticle and cryogenic lubricants with different viscosities were prepared to reduce the wear of Inconel 601. Additionally, the surface is hardened by the pack aluminizing. With the 100 µm thick NiCrAl intermetallic coating layer formed on the surface by the aluminizing process, an improvement was achieved in the hardness (2.9 times) and elasticity modulus values (15%) of the surface. The wear behavior of Inconel 601 was investigated under different loads (15 N, 25 N, 35 N) and using different lubricants (Dry, Nano-MQL-Mix, Cryo-MQL, Cryo-Nano-MQL) in a ball-on-flat wear device. In the studies conducted, the lowest volume loss, friction coefficient and wear depth were achieved in Cryo-Nano-MQL conditions and aluminized samples, while the highest values occurred in a dry environment. When the volume loss results are examined, the average volume loss in the as received samples occurred in a dry environment with 2.76 mm3. When switching from dry environment to Cryo-Nano-MQL at a load of 35 N, a decrease of 96.85% is observed. In alumination samples, the average volume loss occurred in a dry environment with 1.74 mm3. When switching from dry environment to Cryo-Nano-MQL at a load of 35 N, a decrease of 97.70% is observed. Tribological performance was improved by increasing the viscosity of the lubricants used and by using the pack aluminization method.